Training of Geogebra Software to Solve the Problems of Cube and Beam Space in SMP Muhammadiyah 1 Purwokerto - Malim Muhammad; Sigit Sugiyanto (UM Purwokerto Press, 2022)
The development and progress of science and technology are experiencing a rapid increase, including in the field of education. Mathematics is one of the fields of study that is always taught at every level of school education. Along with the increasing development of science and technology, mathematics as a basic science has a very important role. The purpose of this study is to train SMP Muhammadiyah 1 Purwokerto students to improve their practical ability, in this case, the use of the software GeoGebra. This study's subjects are the students and teachers of Muhammadiyah 1 Purwokerto. The study location is SMP Muhammadiyah 1 Purwokerto, with around 44 persons. Implementation of the activities through presenting the material about the program GeoGebra in Cube and Beams in finishing materials. The results of service activities are to overcome the grasp of spatial skills and improve the ability of information and communication technologies in particular mathematical software, in this case, the use of the software GeoGebra as a medium of learning in solving mathematical material in particular, material Beam and Cube.